2004
DOI: 10.1103/physreve.69.046303
|View full text |Cite
|
Sign up to set email alerts
|

Canonical description of ideal magnetohydrodynamic flows and integrals of motion

Abstract: In the framework of the variational principle the canonical variables describing magnetohydrodynamic (MHD) flows of general type (i.e., with spatially varying entropy and nonzero values of all topological invariants) are introduced. It is shown that the velocity representation of the Clebsch type following from the variational principle with constraints is equivalent to that resulting from the generalization of the Weber transformation performed in the paper for the case of arbitrary MHD flows. Using such comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…It can be easily shown that provided that B is in the form given in equation (17), and equation (18) is satisfied, then both equation (1) and equation (2) are satisfied. Since according to equation (16) both ∇ × B and B are parallel it follows that equation (16) can be written as:…”
Section: Sakurai's Variational Principle Of Force-free Magnetohydrodymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be easily shown that provided that B is in the form given in equation (17), and equation (18) is satisfied, then both equation (1) and equation (2) are satisfied. Since according to equation (16) both ∇ × B and B are parallel it follows that equation (16) can be written as:…”
Section: Sakurai's Variational Principle Of Force-free Magnetohydrodymentioning
confidence: 99%
“…The authors of this paper suspect that this number can be somewhat reduced. Moreover, A. V. Kats in a remarkable paper [17] (section IV,E) has shown that there is a large symmetry group (gauge freedom) associated with the choice of those functions, this implies that the number of degrees of freedom can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…From now on the derivation proceeds as in equations (14,15,17) resulting in equations (16,18) and will not be repeated. The difference is that now α, β and σ are not independent quantities, rather they depend through equation (32) on the derivatives of χ i , ν.…”
Section: Lagrangian Density and Variational Analysismentioning
confidence: 99%
“…The difference is that now α, β and σ are not independent quantities, rather they depend through equation (32) on the derivatives of χ i , ν. Thus, equations (14,15,17) are not first order equations in time but are second order equations. Now let us calculate the variational derivative with respect to ν this will result in the expression:…”
Section: Lagrangian Density and Variational Analysismentioning
confidence: 99%
See 1 more Smart Citation